Concepções de leitura e formação continuada: implicações na prática docente - Oliveira, Ilda de Fatima de Lourdes (2013)
This research focuses on the analysis and reflections about the reading conceptions underlying the practice of teachers working with groups of 5th grade students in elementary school, and also on continuing education guidelines in order to develop and work with reading skills. In general, it was aimed at verifying which conceptions are revealed in the discourse and in the practice of such teachers and a few hours of continuing education are able to interfere with these concepts and practice. Reading is one of the most important content to be taught at school, since this skill is necessary for learning other classroom contents. Thus, the questions that were emphasized as the guide of our research were: nowadays, which reading conceptions underlie the pedagogical practice of teachers in the 5th grade of elementary school, in Cascavel city, Brazil; and, what are the effects of a few hours formation in the teachers practice? In order to find answers to these questions, the theoretical approaches used in this research are based on authors who address the conceptions of reading; also on ascending, descending and interactional approaches; and on who defends this latter as the most suitable for the formation of a proficient reader. Accordingly, we also use in our studies authors such as: Solé (1998), Colomer and Camps (2002), Leffa (1996 and 1999), Bakhtin (2003, 2010), Castilla (2009), Geraldi (1988 , 2011), Koch and Elias (2011), Koch (2010), Kleiman (2008) Menegassi (1995 , 2005, 2010). The research also relies on studies of continuing education and applied linguistics. It has a qualitative, an ethnographic and an interventional character. Lesson plans, which were developed by three teachers who were participating in the reading formation, were later analyzed. The research data were collected through questionnaires, audio recording, diary of workshops, documented analysis of lesson plans, and through questions related to the reading practice, which were prepared by teachers before and after a 30-hour-course. As a result of this investigation, it is believed that the continuing education must be permanent, and that reading needs more room in the proposed training. Few hours of courses provided some reflections, and changed consciously the development of reading activities made by those teachers, considering that they often elaborate activities from the interactional reading conception, although they are not always aware of the reasons why such activities are being developed